Iron Oxide-Cobalt Nanocatalyst for O-tert-Boc Protection and O-Arylation of Phenols - Gade, Vilas B; Goswami, Anandarup; Varma, Rajender S; Shelke, Sharad N; Gawande, Manoj B (Nanomaterials (Basel, Switzerland), 2018)
Efficient and general protocols for the O-tert-boc protection and O-arylation of phenols were developed in this paper using a recyclable magnetic Fe₃O₄-Co₃O₄ nanocatalyst (Nano-Fe-Co), which is easily accessible via simple wet impregnation techniques in aqueous mediums from inexpensive precursors. The results showed the catalysts were well characterized by XRD (X-ray Diffraction), ICP-AES (Inductive Coupled Plasma Atomic Emission Spectroscopy), TEM (Transmission Electron Microscopy), TOF-SIMS (Time-Of-Flight Secondary Ion Mass Spectrometry) and XPS (X-ray Photoelectron Spectroscopy). The O-tert-boc protection and O-arylation of phenols was accomplished in good to excellent yields (85–95%) and the catalyst was reusable and recyclable with no loss of catalytic activity for at least six repetitions.
Keywords: phenols; O-arylation; ethers; Fe3O4-Co3O4; magnetic nanocatalysts; O-tert-butoxycarbonylation